ДЕМОГРАФИЧЕСКИЕ ИЗМЕНЕНИЯ В КЫРГЫЗСТАНЕ НА ДАННЫЙ МОМЕНТ (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Demographic aspects of the formation and development of human capital in the southern regions of the Kyrgyz Republic in the modern period are considered in the article. The main attention is paid to the characteristics of demographic dynamics, including indicators of birth, mortality, migration, as well as population structure and age characteristics. The southern regions of the country, including Osh, Jalal-Abad and Batken regions, are characterized by population density, age structure and migration flows. The article emphasizes the role of demographic factors in the development of human capital, such as access to education, health and social services. Special attention is paid to the level of qualification of the population, as well as the influence of external labor migration, which has a significant impact on the economic stability of the region due to the remittances of migrants. It also considers problems and tasks related to the insufficient integration of demographic data in the process of planning social and economic development in the south of the country. The article emphasizes the need to develop complex strategies aimed at improving the quality of human capital, including raising the educational level of the population, providing professional training and improving living conditions. Emphasized relevance of the topic in the context of national development and recommendations for effective use of the demographic potential of the southern regions of Kyrgyzstan.
Keywords: demography, Kyrgyz Republic, human capital, migration, birth rate, death, education, healthcare.